2017
DOI: 10.21276/ijlssr.2017.3.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Lead Accumulation and its Effects on Growth and Biochemical Parameters in Tagetes erecta L

Abstract: Tagetes erecta L. was raised in pots containing soil treated with various concentrations of Pb(NO 3 ) 2 (500, 1000, 1500, 2000 and 2500mg/kg). At maturity plants were separated into root, stem, leaves and inflorescence and lead accumulated in each part was quantified. The effects of lead accumulation on growth was analyzed by the measurement of various growth parameters like root and shoot length, fresh and dry weight of root and shoot and total leaf area per plant. Moreover effect of lead accumulation on bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Studies conducted by Andrade Júnior et al (2019) indicated that V. surinamensis presented medium and high tolerance to Cd. Similar results in the reducing sugar concentration have been found in other species (Shah et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Studies conducted by Andrade Júnior et al (2019) indicated that V. surinamensis presented medium and high tolerance to Cd. Similar results in the reducing sugar concentration have been found in other species (Shah et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the sugar transported to the roots because of starch degradation would be an essential energy substrate for the resumption of respiration, conferring a mechanism of tolerance of the plant against the phytotoxic effect of Cd (Rahoui et al 2015). Similar results in the reducing sugar concentration have been found in other species (Shah et al 2017).…”
Section: Discussionsupporting
confidence: 57%
“…However, it has been reported to be deleteriously impacted by numerous heavy metals. 104 The toxic metals attack different photosynthetic apparatus and cause: (i) the deposition of metals in the plant foliage, 105 (ii) a change in the physiological activity of the chloroplast membrane and distribution of metals in leaf tissues, such as the stomata, mesophyll and bundle sheath, 106 (iii) reduction in the formation of photosynthetic pigments, 107,108 (iv) alteration in the cytosolic enzymes and organics, 109 (v) variation in the supra-molecular level action, especially on photosystem I, photosystem II, membrane acyl liquids and the carrier proteins of the vascular tissues, 110 and (vi) the destruction of enzymes associated with photosynthetic carbon reduction (PCR) and the xanthophyll cycle. 50,110 The decrease in the chlorophyll ratio under metal stress could possibly be due to the destabilization and destruction of peripheral proteins.…”
Section: Heavy Metals In Soils: Source and Availabilitymentioning
confidence: 99%